Ultrafast Non-Förster Intramolecular Donor-Acceptor Excitation Energy Transfer - Athanasopoulos, Stavros (2017)
Ultrafast intramolecular electronic energy transfer in a conjugated donor-acceptor system is simulated using nonadiabatic excited-state molecular dynamics. After initial site-selective photoexcitation of the donor, transition density localization is monitored throughout the S2 → S1 internal conversion process, revealing an efficient unidirectional donor → acceptor energy-transfer process. Detailed analysis of the excited-state trajectories uncovers several salient features of the energy-transfer dynamics. While a weak temperature dependence is observed during the entire electronic energy relaxation, an ultrafast initially temperature-independent process allows the molecular system to approach the S2-S1 potential energy crossing seam within the first ten femtoseconds. Efficient energy transfer occurs in the absence of spectral overlap between the donor and acceptor units and is assisted by a transient delocalization phenomenon of the excited-state wave function acquiring Frenkel-exciton character at the moment of quantum transition.